Philosophy in an age of pluralism : the philosophy of Charles Taylor in question - Taylor, Charles; Tully, James; Weinstock, Daniel M. (Cambridge University Press, 1994)
This is the first comprehensive evaluation of Charles Taylor's work and a major contribution to leading questions in philosophy and the human sciences as they face an increasingly pluralistic age. Charles Taylor is one of the most influential contemporary moral and political philosophers: in an era of specialisation he is one of the few thinkers who has developed a comprehensive philosophy which speaks to the conditions of the modern world in a way that is compelling to specialists in various disciplines. This collection of specially commissioned essays brings together twelve distinguished scholars from a variety of fields to discuss critically Taylor's work. The topics range from the history of philosophy, to truth, modernity and postmodernity, theism, interpretation, the human sciences, liberalism, pluralism and difference. Taylor responds to all the contributions and re-articulates his own views.